Efficient and Selective Electrochemical CO2 to Formic Acid Conversion: A First-Principles Study of Single-Atom and Dual-Atom Catalysts on Tin Disulfide Monolayers - Chen, Guanming; Buraschi, Margherita; Al-Heidous, Rashid; Bonakala, Satyanarayana; El-Mellouhi, Fedwa; Cucinotta, Clotilde S. (Journal of physical chemistry. C, 2024)
Electrochemical CO2 reduction reaction (CO2RR) is a sustainable approach to recycle CO2 and address climate issues but needs selective catalysts that operate at low electrode potentials. Single-atom catalysts (SACs) and dual-atom catalysts (DACs) have become increasingly popular due to their versatility, unique properties, and outstanding performances in electrocatalytic reactions. In this study, we used Density Functional Theory along with the computational hydrogen electrode methodology to study the stability and activity of SACs and DACs by adsorbing metal atoms onto SnS2 monolayers. With a focus on optimizing the selective conversion of CO2 to formic acid, our analysis of the thermodynamics of CO2RR reveals that the Sn-SAC catalyst can efficiently and selectively catalyze formic acid production, being characterized by the low theoretical limiting potentials of −0.29 V. The investigation of the catalysts stability suggests that structures with low metal coverage and isolated metal centers can be synthesized. Bader analysis of charge redistribution during CO2RR demonstrates that the SnS2 substrate primarily provides the electronic charges for the reduction of CO2, highlighting the substrate’s essential role in the catalysis, which is also confirmed by further electronic structure calculations.